Legal Analysis of the Sale and Purchase of Customary Land Rights in the Sentani Tribe Customary Law Community in Jayapura Regency - James Yoseph Palenewen (PT. Multidisciplinary Press Indonesia, 2026)
This study aims to determine the sale and purchase of customary land rights in the Sentani Tribe customary law community in Jayapura Regency and to determine the legal protection for buyers in the sale and purchase of customary land rights in the Sentani Tribe customary law community in Jayapura Regency. The method used in this study is empirical juridical, empirical juridical is a field research by identifying and conceptualizing law as a real and functional social institution in the real life system. The results of this study reveal that the sale and purchase of customary land rights in the Sentani Tribe customary law community in Jayapura Regency must obtain approval from the Ondoafi/Customary Leader who has authority over the land, and attended by witnesses, namely the indigenous people, in addition to the sale and purchase agreement must be ratified by the Sentani Tribe Customary Council, which has the function of holding customary trials to make decisions based on deliberation by means of negotiation and mediation. The decisions taken by the Customary Council must be obeyed by the parties concerned and on the basis of customary governance in accordance with customary law. Meanwhile, legal protection for buyers in the sale and purchase of customary land rights in the Sentani Tribe customary law community in Jayapura Regency is that the parties concerned, both the seller and the buyer, come to the Village or Sub-district Office to make an agreement to measure the land to be sold and the Village Head or Sub-district Head and village officials as witnesses that the sale and purchase has taken place, in addition to that, the land is also immediately registered with the National Land Agency by bringing a customary release letter and other requirements needed for administrative purposes in order to obtain legal certainty and legal protection.